Optimal Interior Partial Regularity for Nonlinear Elliptic Systems for the Case 1<m<2 under Natural Growth Condition. (6th April 2010) - Chen, Shuhong; Tan, Zhong
Abstract : We consider the interior regularity for weak solutions of second-order nonlinear elliptic systems with subquadratic growth under natural growth condition. We obtain a general criterion for a weak solution to be regular in the neighborhood of a given point. In particularly the regularity we obtained is optimal.